2001
DOI: 10.1128/aem.67.12.5420-5424.2001
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay Specific for (1→6) Branched, (1→3)-β- d -Glucan Detection in Environmental Samples

Abstract: (133)-␤-D-Glucans are carbohydrate polymers found in the cell walls of most fungi, some bacteria, yeasts, and higher and lower plants. The molecular weight, degree of (136)-linked side branching, helical conformation, and solubility are the most important factors which determine the biological activities of (133)-␤-D-glucans. The biological activities of (133)-␤-D-glucans include host-mediated antitumor activity (11), adjuvant effects (21), and activation of neutrophils (34), eosinophils (23), macrophages (15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
2
36
1
Order By: Relevance
“…We found that glucan levels correlated significantly with airborne spore counts but not culturable fungal levels, possibly because measures of culturable fungi underestimate the airborne fungal load (10). In addition, different fungal species have different concentrations of (133,136)-␤-D-glucans (11).…”
Section: Discussionmentioning
confidence: 78%
“…We found that glucan levels correlated significantly with airborne spore counts but not culturable fungal levels, possibly because measures of culturable fungi underestimate the airborne fungal load (10). In addition, different fungal species have different concentrations of (133,136)-␤-D-glucans (11).…”
Section: Discussionmentioning
confidence: 78%
“…Finally, a major interest of our approach is the potential antimicrobial spectrum of KP, which may include most microorganisms possessing ␤-glucan in their cell wall, inclusive of yeasts, most filamentous fungi, and some bacteria (5,7,16,21). The observation that an engineered antibody fragment exerts an antimicrobial activity in vitro and in vivo comparable to that displayed by the original KT-scFv could open a new scenario in the biochemistry of antimicrobial peptides for the prevention and therapy of the numerous superficial and systemic diseases caused by the numerous KT-susceptible microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The assay developed by Sander et al (27) has been applied to only a limited number of samples from the work environment, and the EIA described by Blanc et al (2) and Rao et al (23) has been used only to analyze reservoir and airborne dust samples from heavily mold-contaminated houses in New Orleans after the hurricanes Katrina and Rita. A third sensitive EIA makes use of galactosyl ceramide, a receptor specific for ␤-(1,3)-glucans (41), as the capture reagent and of a monoclonal antibody specific for ␤-(1,3)-(1,6)-glucans as the detecting antibody (20). Application of this EIA in population studies has, however, not yet been reported.…”
mentioning
confidence: 99%